2010
DOI: 10.1084/jem.20090821
|View full text |Cite
|
Sign up to set email alerts
|

Attracting AID to targets of somatic hypermutation

Abstract: The process of somatic hypermutation (SHM) of immunoglobulin (Ig) genes requires activation-induced cytidine deaminase (AID). Although mistargeting of AID is detrimental to genome integrity, the mechanism and the cis-elements responsible for targeting of AID are largely unknown. We show that three CAGGTG cis-elements in the context of Ig enhancers are sufficient to target SHM to a nearby transcribed gene. The CAGGTG motif binds E47 in nuclear extracts of the mutating cells. Replacing CAGGTG with AAGGTG in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 49 publications
2
39
2
2
Order By: Relevance
“…Recent studies discovered novel cis-acting elements in the IgL locus of the DT40 chicken B cell line that are both essential and sufficient for AIDmediated sequence diversification (59,60). In addition, it was shown that CAGGTG cis elements in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines (61). Overall, these studies highlight an important role of cis regulatory elements in AID targeting to Ig loci (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies discovered novel cis-acting elements in the IgL locus of the DT40 chicken B cell line that are both essential and sufficient for AIDmediated sequence diversification (59,60). In addition, it was shown that CAGGTG cis elements in the context of Ig enhancers were sufficient and essential to target mutations to a nearby transcribed gene in transgenic DT40 cell lines (61). Overall, these studies highlight an important role of cis regulatory elements in AID targeting to Ig loci (57).…”
Section: Discussionmentioning
confidence: 99%
“…It is not entirely clear how AICDA is recruited to gene regulatory regions, although recruitment by the bHLH transcription factor TCF3 E2A is implicated in this process and enrichment in E-box binding sites in GC B-cell hypomethylated genes is consistent with involvement by this factor. 38,42 AICDA was also shown to be recruited to stalled RNA polymerase II in association with replication protein A (RPA 5 ). Collectively, the data suggest that AICDA contributes to epigenetic programming of the GC B cell by either directly or indirectly mediating CpG demethylation, a notion that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Two copies of the E2A recognition motif was sufficient to enhance SHM of an artificial hypermutable insert within an Igk transgene without affecting the expression of the transgene [53]. Later, it was shown that an artificial GFP-expressing transgene containing just three E2A binding motifs in the context of both Igk enhancers acquired a spectrum of mutations [52]. Furthermore, it was noted that non-Ig genes mistargeted by AID tend to be linked to cis-regulatory elements that contain E-box sites.…”
Section: Aid Targetingmentioning
confidence: 99%